Methodology development for ccalculating productivity and its losses to determine optimization regime in assembly line - Abdul Rahman, Riza
Modern manufacturing system requires high rate productivity with low cost unit price to maintain its competitiveness in global market. To achieve these goal common investigation of productivity in manufacturing especially in assembly line environment consist of two main purposes: (1) To determine potential reserve of productivity in actual production condition, and (2) To provide initial parameter for planning a new process arrangement based on prior experience of actual operating arrangement. The calculation of productivity itself shall easily be applied for various kind of assembly type such manual, automatic or hybrid and also may cover the complexity of various models of products its produces. By using chronometric analysis as the statistical basis, the formulation for productivity calculation must cover all its complexity mathematically. The result of productivity calculation should be compared to graph of price per unit under the same domain to determine the range of optimization regimes. The final result is reliable important data for corporate decision makers to choose the optimum configuration between the most economical configuration and the most productive configuration.